(3GdeTj ddahRs (3HQfGeL Sgd ddMejI h GddjGbI aj (B4 (3CjGes - (3SJhJeGf, aQjO Cjgs; (3ecJHI LQjQs ((3GdQjGVs (3ecJHI LQjQs, 2006)
(3jbOe gPG GdcJGH COdI WHjI KGHJI dG JbHd GdOMV Ydi Cf GJHGY HQfGeL eTj efJXe jbdd GMJeGdGJ GdEUGHI HCeQGV GdbdH, h GdScJGJ GdOeGZjI, hjNaa GdVZW GdYUHj h GdJhJQ, hjSGYO aj EfbGU GdhRf h GdJMce ajg, hjDMQ GdEUGHI HCTcGd eYjfI ef GdJgGH GdeaGUd h GdSQWGfs
(3GdfU eJQLe Edi GddZI GdYQHjI ef GddZI GdEfLdjRjIs
1 9
Keywords: (3CfbGU GdhRfs; (3GddjGbI GdHOfjIs; (3GdeTjs